Differential diagnostics of mesenhymal tumors of uterine corpus founded on immunophenotypes of neoplasms. - Shponka I.S.; Goncharova A.S. (Морфологія, 2011)
Morphological diagnostics of mesenhymal uterine neoplasms is complex due to polymorphism of benign and malignant processes. The purpose of our research was to devise the complex differential diagnostics criterions for foregoing tumors founded on expression's indexes of biological tissue's properties markers studying. We determined, that for smooth muscle tumors with unknown malignant potential diagnostics, it will be an expedient to use as main markers p53, Ki-67, ER, PGR and as auxiliary p21, bax, VEGF, TSP-1, CD34. For differential diagnosis of leiomyomas and endometrial stromal tumors it is neсessary to use СD10, desmin, α-SMA, h-caldesmon, Ki-67. For definition of atypia's level in the tumors of endometrial stroma, the most informative will be diagnostical panel from Ki-67, p53, ER, PGR, and cyclin D1. To solve the issue of histogenesis will help the complex consists of CD10, α-SMA, desmin, та h-caldesmon.